Variants in NAA15 cause pediatric hypertrophic cardiomyopathy. Issue 1 (26th October 2020) - Ritter, Alyssa; Berger, Justin H.; Deardorff, Matthew; Izumi, Kosuke; Lin, Kimberly Y.; Medne, Livija; Ahrens‐Nicklas, Rebecca C.
Abstract: The NatA N‐acetyltransferase complex is important for cotranslational protein modification and regulation of multiple cellular processes. The NatA complex includes the core components of NAA10, the catalytic subunit, and NAA15, the auxiliary component. Both NAA10 and NAA15 have been associated with neurodevelopmental disorders with overlapping clinical features, including variable intellectual disability, dysmorphic facial features, and, less commonly, congenital anomalies such as cleft lip or palate. Cardiac arrhythmias, including long QT syndrome, ventricular tachycardia, and ventricular fibrillation were among the first reported cardiac manifestations in patients with NAA10‐related syndrome. Recently, three individuals with NAA10‐related syndrome have been reported to also have hypertrophic cardiomyopathy (HCM). The general and cardiac phenotypes of NAA15‐related syndrome are not as well described as NAA10‐related syndrome. Congenital heart disease, including ventricular septal defects, and arrhythmias, such as ectopic atrial tachycardia, have been reported in a small proportion of patients with NAA15‐related syndrome. Given the relationship between NAA10 and NAA15, we propose that HCM is also likely to occur in NAA15‐related disorder. We present two patients with pediatric HCM found to have NAA15‐related disorder via exome sequencing, providing the first evidence that variants in NAA15 can cause HCM.